The “Medieval House” of Coimbra: Archeology of architecture in the demystification of archetypes - Ginja, António (2019)
Located in the old medieval outskirts of Coimbra, a residential building has traditionally been named "medieval house”, due to its architecture, consistent with what was in vogue in Portuguese cities of the late medieval period. However, the opening of parietal archaeological surveys in the building revealed techniques, materials and construction systems which were used right until the eighteenth century. The archaeological interpretation and the art-historical analysis of the architecture of the “medieval house” of Coimbra offer a unique opportunity to reflect on some architectural paradigms. Comparing it with other buildings and with iconographic sources, its chronotypology will be analized and the diachrony of the constructive models adopted in this house will be demonstrated. Questioning its chronological epithet, the persistence of certain habits and constructive archetypes will be explored, as well as the tension between private and public spaces, deepened by living and working in the same place.